INFLUENCING FACTORS ANALYSIS OF BANKING LOAN CHANNELING - Achir, Rinda (Jurnal Tepak Manajemen Bisnis, 2014)
According to Bank Indonesiaâs data, loan distribution tends to incr ease from year to year , but they ar e still under expectation which was tar getted to 85%. In the 201 1, the LDR ratio was 78,77%, and it incr eased to 83.58% in 2012. This increase shows that banking intermediary function went to a much better position and more significant in the nations economic development. However , OEOR ratio was still high for it still achieved 70-80%, higher than several South Asia countries who were able to mantain this ratio at only 40-60%. This fact indicates that there is an inefficiency in Indonesiaâs banking.Based on such phenomenon, it is necessary to conduct a research about the influencing factors of banking loan channeling, which covers Return On Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), and Operatinal Expense to Operational Ratio (OEOR). This research uses the twenty (20) listed banks at Bursa Efek Indonesia as objects, with 2008 to 2012 data period. Double reggresion technique was used to analyse the panel data. The t test was used to check the significancy of individual independent variable to dependent variable, while the F test was used to examine the influence of the independent variabel simultanously, with significancy 5%. Research came to the result that Return On Assets (ROA), Non Performing Loans (NPL) and Capital Adequacy Ratio (CAR) partially have a significant impact to banking loan channeling. While Operational Expense to Operational Ratio (OEOR) have a impact but it is not significant to banking loan channeling.Keywords : Banking loan channeling, return on assets, capital adequacy ratio, non performing loans, operatinal expense to operational ratio